2000
DOI: 10.1002/(sici)1097-0142(20000415)88:8<1877::aid-cncr17>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vaginal radical trachelectomy

Abstract: In young patients affected by early invasive cervical carcinoma, radical trachelectomy does not appear to increase the rate of recurrence. It carries a relative risk of infertility and late miscarriage but makes it possible for some patients to become pregnant and give birth to normal newborns. Thus, it seems reasonable to offer this procedure in selected cases, provided that each patient is fully informed and the surgeon properly trained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…If adequate margins are achieved, a cerclage is placed. Dargent 106 covers the cerclage with vaginal epithelium to avoid ascending infections (Saling procedure). Although this procedure is technically feasible, long‐term follow up of adequate numbers of patients is needed to assess survival and pregnancy outcomes.…”
Section: Fertility and Outcomes After Therapy Of Common Cancer Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…If adequate margins are achieved, a cerclage is placed. Dargent 106 covers the cerclage with vaginal epithelium to avoid ascending infections (Saling procedure). Although this procedure is technically feasible, long‐term follow up of adequate numbers of patients is needed to assess survival and pregnancy outcomes.…”
Section: Fertility and Outcomes After Therapy Of Common Cancer Typesmentioning
confidence: 99%
“…Because of these results, several authors recommend oral antibiotic therapy between 14 and 16 weeks to help eradicate vaginal flora, Gram stains to rule out bacterial vaginosis, covering the os with vaginal epithelium, and more frequent visits to detect cervical dilatation (biweekly from 18 to 28 weeks and weekly from 28 weeks until delivery). Dargent 106 has had no cases of preterm delivery since he began the Saling procedure to avoid ascending infections. When cervical incompetence is diagnosed, another cerclage can be placed depending on the trimester.…”
Section: Fertility and Outcomes After Therapy Of Common Cancer Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertility-sparing surgery for early-stage cervical carcinoma has become an accepted part of gynaecological oncology practice during the last two decades. [3][4][5][6] There have been a number of large series reported that demonstrate the efficacy and safety of radical trachelectomy, and confirm that this procedure can deliver a realistic chance of future pregnancy for many women treated for this disease. 3,4 Cervical cone biopsy is regarded as standard treatment for stage-1a1 cervical cancer, but some authors have questioned whether this procedure could be used for the treatment of highly selected stage-1a2 and -1b1 tumours that may not require as radical an excision as that offered by trachelectomy.…”
Section: Discussionmentioning
confidence: 85%
“…In one patient, the first positive node was the common iliac; in all false-negative SNs, the primary cervical tumor was above 2 cm, and there was an isthmus infiltration revealed by the pathologist. Lesion size of above 2 cm is an exclusion criterion for radical vaginal trachelectomy for women with early stage cervical cancer wishing to preserve fertility (23,24) . This may be a possible exclusion criterion in the future for cervical cancer, along with preoperatively diagnosed enlarged lymph nodes, which are now an exclusion criterion in other malignancies (25) .…”
Section: Discussionmentioning
confidence: 99%